Water-contact patterns and socioeconomic variables in the epidemiology of schistosomiasis mansoni in an endemic area in Brazil - e Costa, M. F. F. Lima (1987)
A study was carried out in Comercinho in south-east Brazil where information relating to socioeconomic factors and water contacts was obtained from 290 (99% of the total) households and 1208 (82% of the total) inhabitants, respectively. Stool examinations and physical examinations were performed on 90% and 82% of the population, respectively. The rates of Schistosoma mansoni infection and splenomegaly were higher in families whose heads were manual workers, in individuals living in houses without piped water and of poor construction, and in those who were born in Comercinho. A total of 1017 (84%) individuals reported water contact; 75% of these contacts were for household activities or bathing and 21% for leisure. The faecal egg counts decreased in persons over 15 years of age, while the degree (intensity) of water contact did not. The mean degree of water contact was higher in individuals without than with piped water in the household (96.8±0.6 v. 25.7±0.6). The main risk factors for splenomegaly weer no piped water, intense water contact, bathing in streams, and daily contact (odds ratio=7.3, 5.1, 4.5 and 3.6, respectively). These results indicate that the extension of piped water to houses should decrease the incidence of splenomegaly in this endemic area.